COVID‐19 pandemic in France: health emergency experiences from the field. (22nd June 2020) - Chamboredon, P.; Roman, C.; Colson, S.
Abstract : Aim: This paper describes the situation regarding COVID‐19 emergency in France as of early May 2020, the main policies to fight this virus, and the roles and responsibilities of nurses regarding their work at this time, as well as the challenges facing the profession. Background: Europe continues to be affected by the COVID‐19 pandemic. At the time of writing France was the fourth country with the highest number of detected cases and cumulative deaths. Sources of evidence: Websites of the World Health Organization, French Government, French Agency of Public Health, French National Council of Nurses and ClinicalTrials.gov database, as well as the experiences of the authors. Discussion: The history of the development of the pandemic in France helps explain the establishment of the state of health emergency and containment of the population. Many decisions made had undesirable repercussions, particularly in terms of intra‐family violence, mental health disorders and the renunciation of care. Hospitals and primary care services, with significant investment by nurses, played a key role in the care of persons with and without COVID‐19. Conclusion: France has suffered a very high toll in terms of COVID‐19 morbidity and mortality, and effects on its people, health systems and health professionals, including nurses. Implications for nursing practice: Nurses are recognized for their social usefulness in France. However, it is important to consider the collateral effects of this crisis on nurses and nursing and to integrate the health emergency nursing skills established during the pandemic into the standard field of nursing competence. Implications for nursing policy: The nursing profession has expectations of a reflection on and revision of nursing skills as well as of its valorization in the French healthcare system, notably carried out by the French National Council Order of Nurses.